(untitled) (The Pakistan Development Review, 1986)
Input-Output (1-0) tables of Pakistan’s economy for the year 1975-76 were published by the Pakistan Institute of Development Economics (PIDE) in 1983. They delineated the structure of production of 118 industries together with the disposition of their output by five categories of final demand: consumption expenditures; gross fixed capital formation; changes in stocks; exports; and re-exports. Import have been shown to be absorbed as intermediate inputs as well as destined for final consumption. The present author presented an analytical paper [3], based on the said data-base, in which despite the useful industrial details captured, the predominant agrarian nature of Pakistan’s economy was emphasized. Agricultural sector’s contribution to the total gross domestic product (CDP) at factor cost amounted to 22.1 percent. Although the 1-0 tables identified some 81 manufacturing industries - both large-scale and small-scale - there were only seven industries whose contribution to the total CDP was of any significance. The manufacturing sector, as a whole, contributed only about 11.7 percent of the total CDP. Service industries, construction and the like still account for the rest of the CDP.